HARMONIZATION OF FOREIGN TRADE REGULATION PROCESSES WITH THE REQUIREMENTS OF THE WORLD TRADE ORGANIZATION: UZBEKISTAN’S EXPERIENCE AND ANALYTICAL APPROACH - Jumaboyev , Ixtiyor (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This scientific article provides a comprehensive analysis of the foreign trade activities of the Republic of Uzbekistan, its trade regulation system, and the processes of harmonization with the requirements of the World Trade Organization. During the research, national foreign trade policy, customs administration, tariff and non-tariff instruments, as well as the level of implementation of international trade standards were examined on the basis of statistical and analytical data. The article identifies existing problems in the development of foreign trade and develops scientifically grounded proposals aimed at overcoming them.